En-Gedi: “A Very Large Village of Jews” - Hirschfeld, Y. (Liber Annuus, 2005)
Abstract The people of En-Gedi developed a unique and flourishing economy. Their economic success is expressed not only in the fine synagogue that they built in the center of their village, but also in the high level of construction of their houses. Mosaic floors were uncovered in some of the residential homes, a rare find in villages. Two hoards of gold coins found attest also to the successful commercial activity of some of the inhabitants of En-Gedi. This activity most probably focused on export of perfumes, medicines and Dead Sea Products (bitumen and salt), as well as date palm products (fruit and date honey). The end of the village in the late sixth or early seventh century apparently resulted from an attack by nomads. This phenomenon signals the beginning of the end of Byzantine rule in the east.